2019
DOI: 10.1080/1323238x.2019.1707474
|View full text |Cite
|
Sign up to set email alerts
|

Contentious politics, human rights and Australian immigration detention

Abstract: Australian immigration detention has been a contentious political issue for over two decades.While Australia is signatory to all major human rights instruments, immigration detentions' status as administrative detention, the bipartisan political support it receives and the open hostility the government has expressed for human rights have ensured few avenues for political reform and progress toward the realisation of these rights. While this has challenged more traditional legal and institutional means of pursu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…14 Also illustrative in that regard is the more recent decision of Mortimer J in DBE17 v Commonwealth [2018]. 15 In this matter, the applicant claimed that the detention of members of the group in immigration detention was unconstitutional and therefore invalid, and that as a result they were owed damages for unlawful detention. However, Mortimer J found that the Federal Court had no jurisdiction to determine the proceedings by virtue of s 474AA of the Migration Act 1958 (Cth), dismissing the proceedings.…”
Section: Refugee Law Casesmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Also illustrative in that regard is the more recent decision of Mortimer J in DBE17 v Commonwealth [2018]. 15 In this matter, the applicant claimed that the detention of members of the group in immigration detention was unconstitutional and therefore invalid, and that as a result they were owed damages for unlawful detention. However, Mortimer J found that the Federal Court had no jurisdiction to determine the proceedings by virtue of s 474AA of the Migration Act 1958 (Cth), dismissing the proceedings.…”
Section: Refugee Law Casesmentioning
confidence: 99%
“…This case could be seen to be a human rights case due to it being referrable to Article 14 of the ICCPR. Article 14 requires fairness of procedure for 'suits at law', which can include administrative decision making 15. DBE17 v Commonwealth [2018] FCA 1307 16.…”
mentioning
confidence: 99%